Model of a second-hand goods resale exchange under transactional pricing strategy - Iuliia Iarmolenko; Galyna Chornous (Ekonomika, 2020)
A modern effective business model involves the use of an appropriate pricing strategy. However, what matters is not only short-term profitability but also the long-term loyalty of clients. The main purpose of this paper is to present a specific transactional pricing strategy for a second-hand goods resale exchange platform that allows to avoid the possible negative outcomes of being associated with consumer discrimination. Using a simulation modeling approach, it was shown how customer segmentation combined with transactional pricing can help gain higher profitability. The model is based on the work of intelligent agents that recreate the full product lifecycle. Changing the input parameters of the model, it is possible to simulate different scenarios of a company's activity and market conditions. The model supports the inclusion of any number of products, while its intelligent agents' methods are still flexible to be replaced with other techniques. The simulation model has shown that the use of transactional pricing can increase the profitability of a business while keeping its clients loyal.
Keywords: 330; Transactional Pricing; Pricing Strategy; Simulation Modeling; Consumer Discrimination